2023
DOI: 10.1007/s00134-022-06969-7
|View full text |Cite
|
Sign up to set email alerts
|

Advancing precision-based antimicrobial dosing in critically ill patients

Abstract: Treatment of infections among critically ill patients remains problematic, with ongoing challenges in antimicrobial dosing optimisation. Strategies, such as modelinformed precision dosing (MIPD), may be effective solutions but as yet without documented clinical benefit.In a paper published in the December issue of Intensive Care Medicine, Ewoldt and colleagues conducted the DOLPHIN trial to evaluate whether a MIPD intervention (therapeutic drug monitoring [TDM] and use of dosing software) in critically ill pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Meta-analyses of individualised antimicrobial dose optimisation con rm the achievement of higher rates of target exposures and have suggested reductions in treatment failure and adverse outcomes such as nephrotoxicity [28,29]. More work is undoubtedly necessary to assess the bene t of the approach [30], and it is hoped that ndings from our study provide further impetus to examine this important research question in the context of a suitably powered randomised clinical trial.…”
Section: Discussionmentioning
confidence: 73%
“…Meta-analyses of individualised antimicrobial dose optimisation con rm the achievement of higher rates of target exposures and have suggested reductions in treatment failure and adverse outcomes such as nephrotoxicity [28,29]. More work is undoubtedly necessary to assess the bene t of the approach [30], and it is hoped that ndings from our study provide further impetus to examine this important research question in the context of a suitably powered randomised clinical trial.…”
Section: Discussionmentioning
confidence: 73%
“…Innovative approaches such as wearable biosensors that provide rapid quantification of antibiotic concentrations, could reduce these delays and facilitate earlier TDM and dose optimisation [ 33 ]. More work is undoubtedly necessary to assess the benefit of the approach [ 34 ], and it is hoped that findings from our study provide further impetus to examine this important research question in the context of a suitably powered randomised clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Dosing nomograms, clinician-based predictions, or dosing software (e.g., BestDose ® , Antibiotics kinetics ® , MwPharm++ ® , TDMx ® , etc.) allow for further individual dosage adjustment [ 19 , 20 , 21 , 22 ]. TDM is already successfully implemented on a large scale; A-TEAMICU reported that TDM was used in 61% of ICUs surveilled [ 9 ].…”
Section: Resultsmentioning
confidence: 99%